2023
DOI: 10.1088/1674-1056/ac834b
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic insights into early stage corrosion of bcc Fe surfaces in oxygen dissolved liquid lead-bismuth eutectic (LBE-O)

Abstract: Classical molecular dynamics simulations with global neural network machine learning potential have been used to study early-stage oxidation and dissolution behaviors of bcc Fe surfaces contacting with stagnant oxygen dissolved liquid lead-bismuth eutectic (LBE-O). Both static and dynamic simulation results indicate that the early-stage oxidation and dissolution behaviors of bcc Fe show strong orientation dependence under the liquid LBE environments, which may explain experimental observations of uneven interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…6,7,[88][89][90][91] Currently, MLPs have already been extensively utilized in the study of bulk liquid 92,93 and solid battery materials, [94][95][96] especially to investigate their transport properties. 91,[97][98][99] Some studies have demonstrated the possibility to model interfaces with MLPs, [100][101][102][103][104][105] even though these interfaces are not held at constant potentials and may not be related to batteries. Such achievements indicate the potential feasibility of integrating constant-potential MD with MLPs in comprehending the intricate interfacial chemistries of batteries.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…6,7,[88][89][90][91] Currently, MLPs have already been extensively utilized in the study of bulk liquid 92,93 and solid battery materials, [94][95][96] especially to investigate their transport properties. 91,[97][98][99] Some studies have demonstrated the possibility to model interfaces with MLPs, [100][101][102][103][104][105] even though these interfaces are not held at constant potentials and may not be related to batteries. Such achievements indicate the potential feasibility of integrating constant-potential MD with MLPs in comprehending the intricate interfacial chemistries of batteries.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Dissolution in LBE is one of the basic forms of liquid LBE corrosion. When the steel material is in liquid LBE, the metal elements in the steel material will dissolve into the liquid LBE at a low oxygen (CO < 5 × 10 −7 wt%) concentration [9,12,32,38,44,45] (Figure 1) [46]. This is usually characterized by the transfer of material components for example, Ni, Fe, or Cr to the liquid phase, continuing until saturation [14].…”
Section: Dissolution Corrosionmentioning
confidence: 99%
“…Dissolution experiments of 316L were conducted in LBE, and preferential dissolution of Ni was observed after temperature control at 500 • C for 3000 h. The analysis concluded that the dissolution kinetics of 316L were controlled by the dissolution reaction rate of Ni [10]. Since the solubility and dissolution rate of metal elements in liquid LBE vary greatly, the degree of corrosion of materials in liquid LBE varies [9,[32][33][34]. As the dissolution speed of Ni in LBE is large, the higher the Ni element content of the material, the more severe the dissolution corrosion will be.…”
Section: Dissolution Corrosionmentioning
confidence: 99%
See 1 more Smart Citation